Comparative Analysis of the Chloroplast Genomes of the Chinese Endemic Genus Urophysa and Their Contribution to Chloroplast Phylogeny and Adaptive Evolution - Xie, Deng-Feng (Int J Mol Sci, 2018)
Urophysa is a Chinese endemic genus comprising two species, Urophysa rockii and Urophysa henryi. In this study, we sequenced the complete chloroplast (cp) genomes of these two species and of their relative Semiquilegia adoxoides. Illumina sequencing technology was used to compare sequences, elucidate the intra- and interspecies variations, and infer the phylogeny relationship with other Ranunculaceae family species. A typical quadripartite structure was detected, with a genome size from 158,473 to 158,512 bp, consisting of a pair of inverted repeats separated by a small single-copy region and a large single-copy region. We analyzed the nucleotide diversity and repeated sequences components and conducted a positive selection analysis by the codon-based substitution on single-copy coding sequence (CDS). Seven regions were found to possess relatively high nucleotide diversity, and numerous variable repeats and simple sequence repeats (SSR) markers were detected. Six single-copy genes (atpA, rpl20, psaA, atpB, ndhI, and rbcL) resulted to have high posterior probabilities of codon sites in the positive selection analysis, which means that the six genes may be under a great selection pressure. The visualization results of the six genes showed that the amino acid properties across each column of all species are variable in different genera. All these regions with high nucleotide diversity, abundant repeats, and under positive selection will provide potential plastid markers for further taxonomic, phylogenetic, and population genetics studies in Urophysa and its relatives. Phylogenetic analyses based on the 79 single-copy genes, the whole complete genome sequences, and all CDS sequences showed same topologies with high support, and U. rockii was closely clustered with U. henryi within the Urophysa genus, with S. adoxoides as their closest relative. Therefore, the complete cp genomes in Urophysa species provide interesting insights and valuable information that can be used to identify related species and reconstruct their phylogeny.